Experimental determination of the effective point of measurement and the displacement correction factor for cylindrical ionization chambers in a 6 MV photon beam - Legrand, Carine; Hartmann, Günther H.; Karger, Christian (Physics in medicine and biology, 2012)
The displacement effect of cylindrical ionization chambers is taken into account either by an effective point of measurement (EPOM) or, alternatively, by using a displacement correction factor. The dependence of these effects on water was examined as a function of the cavity radius for 60Co gamma radiation in a previous paper. This paper describes results for high-energy photon beams using the same measurement technique. Additionally, the displacement correction factor was directly measured. Absorbed doses measured under reference conditions following the international protocol IAEA TRS-398 and the German protocol DIN 6800-2 agreed well between the chambers with different cavity radii within a standard uncertainty of 0.2%. However, there was a constant difference of 0.2% between both protocols. Similar to our observations made in 60Co, absorbed doses measured with the different chambers at depths beyond the maximum showed deviations of up to 0.6% and 0.5% for IAEA TRS-398 and DIN 6800-2, respectively, and deviations of more than 1% were found for both protocols in the build-up and maximum region. We therefore propose modified formulas for the determination of the EPOM and the displacement correction factor.